The role and progress of silver nanowires in wearable strain sensors for human motion detection - Hejin Wang; Ji Jiang; Jiuyang Wang (Alexandria Engineering Journal)
Silver nanowires (AgNWs) have emerged as a promising material for the development of wearable strain sensors due to their excellent electrical conductivity, optical transparency, and mechanical flexibility. This review comprehensively explores the recent advancements and trends in AgNW-based strain sensors for human motion detection. We discuss the fundamental aspects of stretchable strain sensors, the synthesis and properties of AgNWs, and the fabrication techniques for AgNW-based sensors, including solution processing, patterning, printing, and hybridization with other nanomaterials. The applications of these sensors in monitoring joint movements, physiological signals, and gesture recognition are highlighted. Furthermore, we address the challenges and future perspectives in this field, focusing on achieving high sensitivity and stretchability simultaneously, long-term stability and durability, scalable and cost-effective manufacturing, and the potential for multi-modal and self-powered sensing. With ongoing advancements in materials science and manufacturing technologies, AgNW-based strain sensors have the potential to revolutionize wearable and flexible electronics for various applications in healthcare, sports, and human-machine interfaces.